2018
DOI: 10.1080/07038992.2019.1579051
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Incidence Angle in the Correlation of C-band Polarimetric Parameters with Biophysical Variables of Rain-fed Crops

Abstract: A multi-temporal field experiment was conducted within the Soil Measurement Stations Network of the University of Salamanca (REMEDHUS) in Spain in order to retrieve useful crop information. The objective of this research was to evaluate the potential of polarimetric observations for crop monitoring by exploiting a time series of 20 quad-pol RADARSAT-2 images at different incidence angles (i.e., 25º, 31º and 36º) during an entire growing season of rainfed crops, from February to July 2015. The time evolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The present research is aimed at extending the use of a time series of polarimetric observables for land-cover classification, mainly focussed over agricultural fields. This possibility was previously identified [42] when several crop parameters were tested against radar measurements. The difference found in the correlations for different crop types suggested that specific crops, mainly cereal types, could be classified using SAR observables.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The present research is aimed at extending the use of a time series of polarimetric observables for land-cover classification, mainly focussed over agricultural fields. This possibility was previously identified [42] when several crop parameters were tested against radar measurements. The difference found in the correlations for different crop types suggested that specific crops, mainly cereal types, could be classified using SAR observables.…”
Section: Introductionmentioning
confidence: 88%
“…Since Sentinel-1 is dual-pol, only one scenario was explored (G) for this satellite. Scenario E was created after previous research [42], where it was found that the differences in the correlation between SAR observables and biophysical parameters among crop types suggested the possibility of classifying crops with these SAR observables. Scenario F was generated to compare the dual-pol data from RADARSAT-2 against Sentinel-1.…”
Section: Classification Scenariosmentioning
confidence: 99%
“…The uniform image acquisition beam mode As shown in Table 1, seven fully polarimetric C-band RADARASAT-2 images in FQ10W (Fine-Quad Wide) covering the entire growing season from April to September in 2015 were employed. The uniform image acquisition beam mode offers the advantage of reduced complexity caused by varying SAR incidence angles for multitemporal stud-ies [35][36][37]. In particular, except for the date on 30 May, when the satellite did not overpass our study area to acquire imagery due to user conflicts, the time interval between data acquisitions was 24 days.…”
Section: Study Site and Datasetmentioning
confidence: 99%
“…On the other hand, the data in some cases are acquired using different beam modes with different spatial resolutions and incidence angles (e.g., RADARSAT-2 launched by the Canadian Space Agency). In particular, incidence angle has shown to affect the polarimetric parameters and classification performance [35][36][37]. Moreover, the number and types of selected PolSAR parameters for investigating temporal variation are also limited, such as SAR backscattering and ratios, polarimetric decomposition parameters, polarimetric coherences and phase differences.…”
Section: Introductionmentioning
confidence: 99%
“…Other parameters were also estimated (e.g., plant height, chlorophyll) but were discarded here as they were collected at plant level. Table 1 listed the selected parameters, which aimed to describe both the state of the plant and their rate of activity [34], and have been largely used in remote sensing applications to agronomy [35][36][37]. Two replicates of plant samples were taken at association level over a circular fenced area of 0.125 m 2 , together with zenithal photographs taken at a same height of 1.5 m, following the protocol of Sánchez et al [38].…”
Section: Field and Laboratory Estimationsmentioning
confidence: 99%